When the Eyes No Longer Lead: Familiarity and Length Effects on Eye-Voice Span - Silva, Susana; Reis, Alexandra; Casaca, Luís; Petersson, Karl M.; Faísca, Luís (Frontiers in Psychology, 2016)
During oral reading, the eyes tend to be ahead of the voice (eye-voice span). It has been hypothesized that the extent to which this happens depends on the automaticity of reading processes, namely on the speed of print-to-sound conversion. We tested whether EVS is affected by another automaticity component - immunity from interference. To that end, we manipulated word familiarity (high-frequency, low-frequency and pseudowords) and word length as proxies of immunity from interference, and we used linear mixed effects models to measure the effects of both variables on the time interval at which readers do parallel processing by gazing at word N+1 while not having articulated word N yet (offset eye-voice span). Parallel processing was enhanced by automaticity, as shown by familiarity x length interactions on offset eye-voice span, and it was impeded by lack of automaticity, as shown by the transformation of offset eye-voice span into voice-eye span (voice ahead of the offset of the eyes) in pseudowords. The relation between parallel processing and automaticity was strengthened by the fact that offset eye-voice span predicted reading velocity. Our findings contribute to understand how the offset eye-voice span, an index that is obtained in oral reading, may tap into different components of automaticity that underlie reading ability, oral or silent. In addition, we compared the duration of the offset eye-voice span with the average reference duration of stages in word production, and we saw that the offset eye-voice span may accommodate for more than the articulatory programming stage of word N.